Influence of the cementitious paste composition on the E-modulus and heat of hydration evolutions - Maia, Lino (2011)
E-modulus and heat of hydration are features of cement-based materials that follow a rapid rate of change at early ages. This paper analyses the influence of the composition of cementitiouspastes on these features by using two methods: (i) a novel technique for continuously monitoring the E-modulus of cement-based materials, based on evaluating the first resonant frequency of a composite beam containing the material under testing, and (ii) an isothermal calorimeter to determine the released heat of hydration. Seventeen mixes are tested, encompassing pastes with five w/c ratios, as well as different contents of limestone filler, fly ash, silica fume and metakaolin. The results permit the comparison of the E-modulus and heat of hydration sensitivities to mix compositionchanges, and to check possible relations between these features. This work also helps to establish the technique (i) as a non-destructive method for monitoring the E-modulusevolution in cement-based materials since casting.